Partition, partisanship and inter-church relations in Mizoram - Lalnuntluanga, John (Transformation, 2024)
This article is an attempt at identifying ways and means to gauge the construction and reification of ethnicity and socio-cultural identity among Mizo Presbyterians and Mizo Baptists. This is to be done against the backdrop of exercises in cartography and the partitioning of communities undertaken by the colonial administrators. It takes into account the erecting of geospatial boundaries and the creation of specific identities limited to and centred on such demarcations. And it proposes that in instances of a definite lack of sufficient historical sources, it is imperative that one harnesses imagination, the ability of the mind to be creative or resourceful.